Microbiota-Derived Short-Chain Fatty Acids: New Road in Colorectal Cancer Therapy - Sara Gomes; Fátima Baltazar; Elisabete Silva; Ana Preto (Pharmaceutics, 2022)
The colon microbiota is an important player in colorectal cancer (CRC) development, which is responsible for most of the cancer-related deaths worldwide. During carcinogenesis, the colon microbiota composition changes from a normobiosis profile to dysbiosis, interfering with the production of short-chain fatty acids (SCFAs). Each SCFA is known to play a role in several biological processes but, despite their reported individual effects, colon cells are exposed to these compounds simultaneously and the combined effect of SCFAs in colon cells is still unknown. Our aim was to explore the effects of SCFAs, alone or in combination, unveiling their biological impact on CRC cell phenotypes. We used a mathematical model for the prediction of the expected SCFA mixture effects and found that, when in mixture, SCFAs exhibit a concentration addition behavior. All SCFAs, alone or combined at the physiological proportions founded in the human colon, revealed to have a selective and anticancer effect by inhibiting colony formation and cell proliferation, increasing apoptosis, disturbing the energetic metabolism, inducing lysosomal membrane permeabilization, and decreasing cytosolic pH. We showed for the first time that SCFAs are specific towards colon cancer cells, showing promising therapeutic effects. These findings open a new road for the development of alternatives for CRC therapy based on the increase in SCFA levels through the modulation of the colon microbiota composition.